DInSAR for Geomechanical Reservoir Analysis – Application to Reservoir Lagunillas Lower 07, Lake Maracaibo, Venezuela - González Freites, Dario Antonio; Zambrano Mendoza, Orlando; Barrios, Jorge Luis (Rev. Téc. Fac. Ing. Univ. Zulia, 2024)
This study addresses the issue of subsidence in the Lagunillas Inferior 07 (LGINF-07) field in the Lake Maracaibo Basin, Venezuela, a major concern for the oil industry due to ground movements recorded since 1926 that have impacted oil platforms. The objective was to apply the Differential Interferometric Synthetic Aperture Radar (DInSAR) technique to monitor subsidence and provide accurate data without the need for physical presence in the field. TerraSAR-X satellite images, obtained between 2011 and 2015, were processed using differential interferometry to detect ground deformations. The results showed an average subsidence rate of -0.035 meters per year, allowing for the update of geomechanical models and improving the understanding of soil movements in the region, contributing to the planning and safety of oil operations. This analysis, compared with historical data, revealed the effectiveness of DInSAR in predicting future ground movements and optimizing infrastructure management in critical areas of the oil industry. In conclusion, the DInSAR technique is a valuable tool for geomechanical monitoring, improving the safety and efficiency of strategic operations.